Comparison between huperzine A, tacrine, and E2020 on cholinergic transmission at mouse neuromuscular junction in vitr - Lin Jia-Hui; Hu Guo-Yuan; Tang Xi-Can (Acta Pharmacologica Sinica, 2016)
AIM: To compare the effects of huperzine A (Hup A), tacrine, and E2020 on cholinergic transmission at mouse neuromuscular junction in vitro. METHODS: The isolated mouse phrenic nerve-hemidiaphragm preparations were used with the conventional intracellular recording technique. The miniature end-plate potentials (MEPP), the mean quantal content of end-plate potentials (EPP), and the resting membrane potentials of muscle fiber were recorded. RESULTS: Hup A, tacrine, and E2020 at the concentration of 1.0 mumol.L-1 increased the amplitude, time-to-peak, and half-decay time of MEPP in the potencies of E2020 > Hup A > tacrine. Hup A did not significantly change the frequency of MEPP, the appearance of giant MEPP or slow MEPP, the resting membrane potentials, and the mean quantal content of EPP. CONCLUSION: Hup A is a selective and potent cholinesterase inhibitor, by which activity it facilitates the cholinergic transmission at mouse neuromuscular junction, and devoid of pre- and post-synaptic actions.